Experimental and Theoretical Analysis of a Hybrid FRP Strengthening Technique for Reinforced Concrete Circular Columns - Kittipoom Rodsin; Rattapoohm Parichatprecha (Journal of Natural Fibers, 2025)
This study presents a preliminary experimental and analytical investigation into the effectiveness of newly developed hybridized basalt fiber-reinforced polymers and e-glass (B-CHSM) jackets. Twenty-four RC specimens were fabricated, with variables including unconfined compressive strength and the number of B-CHSM layers. The experimental results demonstrated significant enhancements in compressive strength and strain, with improvements of up to 325% and 322%, respectively, compared to unconfined specimens. Specimens with an unconfined strength of 15.5 MPa achieved a 325% increase in ultimate strength with three-layer B-CHSM confinement. For low unconfined strength specimens, strain improvements of 135%, 218%, and 322% were observed with 1-, 2-, and 3-layer B-CHSM confinement, respectively. Low-strength specimens strengthened with 1-, 2-, and 3-layer confinement showed 30%, 22%, and 88% higher ultimate strength than medium-strength specimens and 75%, 75%, and 165% higher strength than high-strength specimens. The study evaluated existing analytical models for FRP strengthening, revealing their limitations in accurately predicting the performance of B-CHSM-confined concrete. Consequently, regression-based expressions were developed, achieving coefficients of determination exceeding 0.80. These expressions were utilized to idealize the stress-strain curves, enabling precise representation of B-CHSM-confined concrete behavior. The predicted curves closely matched experimental results, confirming the reliability of the proposed methodology.
Keywords: Structural Behavior of Reinforced Concrete; Structural Load-Bearing Analysis; Concrete Corrosion and Durability